Religiosity and Emotional Regulation Predicting Resilience in Ghosting Victims: Kekuatan Keagamaan dan Pengaturan Emosi dalam Memprediksi Ketahanan pada Korban Ghosting - Ardiansah, Mohamad Fani Bagas; Hazim, Hazim (Indonesian Journal of Islamic Studies, 2025)
Background: Resilience is an essential psychological factor that enables individuals to adapt positively to emotional challenges. Specific Background: Ghosting, a phenomenon prevalent among young adults, can lower psychological well-being. Knowledge Gap: Limited research has explored how religiosity and emotional regulation jointly contribute to resilience in ghosting victims. Aim: This study aims to examine the simultaneous and partial roles of religiosity and emotional regulation in predicting resilience. Results: Regression analysis showed that religiosity and emotional regulation significantly predict resilience, with emotional regulation contributing more strongly than religiosity. Novelty: This research provides new insights by addressing resilience within the unique context of ghosting, which has rarely been studied in psychological research. Implications: Findings emphasize the importance of integrating spiritual guidance and emotional regulation training in counseling and educational settings to improve resilience among young adults. Highlights : Religiosity and emotional regulation predict resilience Emotional regulation contributes the most Findings guide counseling for ghosting victims Keyword: Religiosity, Emotional Regulation, Resilience, Ghosting, Young Adults